Upaya Meningkatkan Aktivitas dan Hasil Belajar Peserta Didik Melalui Pemberian Reward dan Punishment pada Mata Pelajaran Matematika - ERNI SUHARTI (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
During the learning process students tend to be passive and learning is centered on the teacher, so activity and learning outcomes are low. One of the efforts that can be done is the provision of rewards and punishments during the learning process. The purpose of this study was to increase student activity and learning outcomes through the provision of rewards and punishments. This type of research is classroom action research using a qualitative approach, which is supported by a quantitative approach. This research consists of four stages, namely planning, action, observation, and reflection. This study involved 33 students of class XI MIPA 3 SMAN 8 Padang. Research data obtained through observation sheets, quizzes, learning outcomes tests, and field notes. The data analysis technique used is descriptive analysis. Based on research data in first and second cycles, it shows that the activities and learning outcomes of students have increased. This is indicated by an increase in learning outcomes from 40% in the first cycle to 67% in the second cycle. So, it can be concluded that learning by giving rewards and punishments could increase students' activities and learning outcomes.